The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/a0038287
|View full text |Cite
|
Sign up to set email alerts
|

The visible ground surface as a reference frame for scaling binocular depth of a target in midair.

Abstract: The natural ground surface carries texture information that extends continuously from one’s feet to the horizon, providing a rich depth resource for accurately locating an object resting on it. Here, we showed that the ground surface’s role as a reference frame also aids in locating a target suspended in midair based on relative binocular disparity. Using real world setup in our experiments, we first found that a suspended target is more accurately localized when the ground surface is visible and the observer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
0
14
1
1
Order By: Relevance
“…We also tested the complementary scenario, where the visible surface was the ceiling rather than the ground. However, we did not predict a strong effect of attention, owing to the lower field bias of attention 12 and/or insufficient visual representation of the ceiling surface in the upper field 1315 .…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…We also tested the complementary scenario, where the visible surface was the ceiling rather than the ground. However, we did not predict a strong effect of attention, owing to the lower field bias of attention 12 and/or insufficient visual representation of the ceiling surface in the upper field 1315 .…”
contrasting
confidence: 85%
“…Since ground representation is the reference frame for locating a target in mid-air 15,1921 , attention should affect spatial perception above the ground surface, that is, the volume of perceptual space extending from the observer’s eyes to the ground surface representation. To investigate this, we modified the stimuli in Experiment 1 by placing the target at eye level instead of having it coplanar with the textured surface and by presenting both the ground-texture and ceiling-texture backgrounds simultaneously (Experiment 2, Fig.…”
mentioning
confidence: 99%
“…1, bottom) and linear perspective (lines formed by intersections between the walls and floor/ceiling planes), and either cue could have been responsible for the differences between VEs. Experimental manipulation of linear perspective cues affects perceived distance, perhaps by influencing perceived eye level (Wu, Zhou, Shi, He, & Ooi, 2015). It is therefore possible that the linear perspective cue was responsible for judgment differences across the two VEs.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, several studies have shown that relative binocular disparity information can affect relative depth judgment in the intermediate distance range. [20][21][22][23][24] This being the case, would it be possible that the visual system also uses the relative binocular depth information in the intermediate distance range to judge the absolute (egocentric) distance between the observer and target? A recent study of observers with normal binocular vision from our laboratory reveals that this is possible, at least in the reduced cue environment where the predominant visual depth cues were texture gradient and relative binocular disparity.…”
mentioning
confidence: 99%
“…A recent study of observers with normal binocular vision from our laboratory reveals that this is possible, at least in the reduced cue environment where the predominant visual depth cues were texture gradient and relative binocular disparity. 24 We showed that the relative binocular disparity between a target suspended in midair and the ground surface was used to improve the accuracy of perceived absolute distance. If the visual system also capitalizes on the relative binocular disparity information of the suspended target and the ground surface in the full cue environment where there are ample other monocular cues, as used in the present study, we can hypothesize that strabismic observers with poor stereopsis will not be able to judge accurately the location of a suspended target in the intermediate distance range.…”
mentioning
confidence: 99%